Predictive Value of the Inflammatory Burden Index for Pathological Complete Response in HER2-Positive and Triple-Negative Breast Cancer Receiving Neoadjuvant Chemotherapy: A Comparative Analysis with Conventional Inflammatory Indices - Merve Turan; Özge Demirkıran (Journal of Clinical Medicine, 2026)
Background/Objectives: The inflammatory burden index (IBI), calculated as C-reactive protein (CRP) multiplied by the neutrophil-to-lymphocyte ratio (NLR), has demonstrated prognostic value across several solid tumors. Its role in breast cancer, however, has not been investigated. This study evaluated whether pretreatment or post-treatment IBI could predict pathological complete response (pCR) in patients with HER2-positive or triple-negative breast cancer (TNBC) receiving neoadjuvant chemotherapy (NAC). Methods: This single-center retrospective study included 61 patients who completed NAC followed by surgery between 2019 and 2025. IBI was calculated before and after NAC, and the treatment-related change (ΔIBI) was assessed. Conventional inflammatory indices, including NLR, platelet-to-lymphocyte ratio (PLR), lymphocyte-to-monocyte ratio (LMR), systemic immune-inflammation index (SII), systemic inflammation response index (SIRI), C-reactive protein-to-albumin ratio (CAR), and absolute lymphocyte count (ALC), were evaluated for comparison. Analyses included Mann–Whitney U tests, paired Wilcoxon signed-rank tests, receiver operating characteristic (ROC) curve analysis, and multivariable logistic regression. Results: Twenty-nine patients (47.5%) achieved pCR. No pretreatment or post-treatment inflammatory index was significantly associated with pCR. In paired within-patient analysis, IBI increased significantly during treatment only in patients achieving pCR (p = 0.036), while remaining unchanged in the non-pCR group (p = 0.627). CAR showed an identical pattern, increasing exclusively in the pCR group (p = 0.013). This selective rise was not observed for any index lacking a CRP component and was independent of molecular subtype, anti-HER2 therapy, and chemotherapy regimen. On ROC analysis, ΔCAR yielded the highest area under the curve (AUC) among all inflammatory indices (0.637; p = 0.067), followed by ΔIBI (0.606; p = 0.157); neither reached statistical significance. Ki-67 was the only independent predictor of pCR (AUC 0.724; p = 0.003; optimal cutoff ≥25%). Conclusions: This is the first study to evaluate IBI in HER2-positive and TNBC receiving NAC. Static IBI values did not predict pCR. The selective rise in IBI and CAR during treatment in patients achieving pCR—two independently formulated CRP-based indices showing an identical pattern—suggests that the CRP component carries the biologically relevant signal. This hypothesis-generating observation warrants prospective validation in larger cohorts.